OPTIMIZATION OF DOOR SYSTEM PARAMETERS BASED ON ORTHOGONAL DESIGN - WANG ZhenJiang; HE Zao; SUN Run (Jixie qiangdu)
Taking the left-front door of a type of car as the study object, the method which combined multipurpose optimal method with orthogonal experimental design was applied to parameters optimization design of the thickness of the door system components. Hyperworks software was used to establish a car door finite element analytical model on which a modal and stiffness analysis was performed, and then modal test and stiffness test were proceeded to testify and analyze the correctness of the model. Sensitivity analysis was conducted on each performance of the car door system with car door plate’s thickness being the variable; a car door plate thickness with comparative large influence on car door performance was selected as the controlling factor; a comprehensive performance evaluation function for car door system was constructed with the adoption of weighted sub-goals multiplying and dividing calculations; the orthogonal experimental design was applied to the parametric optimization design on car door system’s comprehensive performance. Finally, the best combinations of all components’ thickness parameters for car door system were got.